Beyond quality : an agenda for improving manufacturing capabilities in developing countries - Wilson, Steven R. (E. Elgar, 1995)
The views expressed in this publication are those of the authors and do not necessarily reflect the views of the Secretariat of the United Nations Industrial Development Organization. The description and classification of countries and territories used, and the arrangement of the material, do not imply the expression of any opinion whatsoever on the part of the Secretariat concerning the legal status of any country, territory, city or area, or of its authorities, or concerning the delimitation of its frontiers or boundaries, or regarding its economic system or degree of development. Designations such as 'developed', 'industrialized' and 'developing' are intended for statistical convenience and do not necessarily express a judgement about the stage reached by a particular country or area in the development process. Mention of firm names and commercial products does not imply the endorsement of the United Nations Industrial Development Organization.